ANALISIS TINGKAT KESEJAHTERAAN PETANI RUMPUT LAUT DI KELURAHAN PABIRINGA, KECAMATAN BINAMU, KABUPATEN JENEPONTO - Al-Basrah, Muh. Ammar Zhafran; Ibrahim, Ibrahim; Falihin, Dalilul; Rusdi, Rusdi; Amirullah, Amirullah (UNM Geographic Journal, 2024)
This research was conducted to find out 1) What is the level of welfare of seaweed farmers in Pabiringa Village, Binamu District, Jeneponto Regency 2) What faktors influence the level of welfare of seaweed farmers in Pabiringa Village, Binamu District, Jeneponto Regency 3) What is the impact on the level of welfare of seaweed farmers sea in Pabiringa Village, Binamu District, Jeneponto Regency 3) What is the impact of the level of welfare of marine seaweed farmers on the sosial life of the community in Pabiringa Village, Binamu District, Jeneponto Regency. The type of research used is descriptive qualitative research. Meanwhile, data collection techniques in this research were carried out using observation, interviews and documentation. Data analysis used in this research is data collection, data reduction, data presentation, and drawing conclusions. This research discusses the level of welfare of grass farmers in Pabiringa sub-district, Jeneponto Regency. The results of this research can influence the level of welfare of seaweed farmers in Pabiringa Village, according to the BKKBN, including at the prosperous family stage III level, because there are several points that are not fulfilled in the Prosperous Family III Plus (KS-III Plus) stage. Faktors that influence farmers' welfare can be seen from the weather, the large number of stretches of seaweed and the low price of seaweed.